Efficacy of Submucosal Injection of Chymotrypsin, Oral Serratiopeptidase or Oral Dexamethasone in Reducing Postoperative Complications Following Impacted Lower Third Molar Surgery: A Prospective, Randomized, Double-Blind, Controlled Clinical Trial - Al-Moraissi, Essam Ahmed; Al-Zendani, Elham Aziz; Al-Selwi, Abeer Mohammed (Frontiers in Oral Health, 2020)
Aim The study aimed to compare between chymotrypsin, oral serratiopeptidase, and oral dexamethasone following impacted mandibular third molars surgery in respect of postoperative complications. Materials and method: A randomized, double-blind clinical trial was conducted on 60 patients who were candidates for impacted mandibular third molars surgery and randomly allocated into the following 3 groups: submucosal chymotrypsin (5 mg), oral serratiopeptidase (10 mg), and oral dexamethasone (8 mg) (each group = 20). The outcome variables were postoperative pain (via visual analog scale), facial swelling (via tape method) and maximal mouth opening immediately after 2nd, 3rd, and 5th postoperative days. Results: A total of 60 patients underwent randomization and allocation concealment and were included in the current study. All of the subjects tolerated the medicines with no untoward side or adverse effects. There was no statistically significant difference between the three groups in respect of postoperative pain intensity, facial swelling and maximal mouth opening at the immediate first hour, 2nd, 3rd, and 5th postoperative days (P < 0.05). Conclusion: The present randomized clinical trial concluded that preemptive sub-mucosal injection of chymotrypsin yields a comparable effectiveness in decreasing postoperative sequelae following impacted mandibular third molars surgery when compared to oral serratiopeptidase or dexamethasone. This is the first Randomized Clinical Trail that assessed efficacy and safety of sub-mucosal injection of chymotrypsin after impacted mandibular third molars surgery. This trial is registered at clinicaltrials.in.th, number (TCTR20200828006).